If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3n^2-14=-9n
We move all terms to the left:
3n^2-14-(-9n)=0
We get rid of parentheses
3n^2+9n-14=0
a = 3; b = 9; c = -14;
Δ = b2-4ac
Δ = 92-4·3·(-14)
Δ = 249
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-\sqrt{249}}{2*3}=\frac{-9-\sqrt{249}}{6} $$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+\sqrt{249}}{2*3}=\frac{-9+\sqrt{249}}{6} $
| 2/8=g/4 | | 5/35=1/a | | 6=-8v+6(v+2) | | 2/5c=24 | | 3(x)-7x-51=0 | | 4(2y+5)-2(y-3=8(2y+4) | | (2x+1)(3-x)+1=(5-x)2x-1)+3x | | 2.25x=6x-79 | | 4/5m*5=24 | | 2(x-1)/2-1/3(x+1)=32x/4 | | 2/9=10y | | -2x-39=5(2x-3) | | 2(2x-1)-4=-38 | | 0.05=(200/x)+0.03 | | x9(x−6)=18 | | 3(x-3)-(2x+1)=4x-2(2-x) | | -5=-(5/4)8+b | | 5x+11=2(3x+4) | | 3×^2-6x=0 | | -5=-5/4(8)+b | | 3(3x+5)=-5x+1 | | 2x-6+5x=4+3x | | 3z/8-6=10 | | 323=17s | | 40=8j | | (5x+15)-8x+40)=(x-65) | | 17=c-14 | | H=-16t^2+168t+9 | | 11q=-187 | | 92=g+30 | | 2x+3/x+4=x-1 | | 2m=82 |